Determination of a Tentative Epidemiological Cut-Off Value (ECOFF) for Dalbavancin and Enterococcus faecium - Robert E. Weber; Carola Fleige; Franziska Layer; Bernd Neumann; Michael Kresken; Guido Werner (Antibiotics, 2021)
Dalbavancin is a lipoglycopeptide antibiotic that shows potent activity against Gram-positive bacteria. It circumvents vanB-type glycopeptide resistance mechanisms; however, data on the in vitro activity of dalbavancin for Enterococcus faecium (E. faecium) are scarce, and thus, no breakpoints are provided. In recent years, there has been a continuing shift from vanA-type to vanB-type vancomycin-resistance in enterococci in Central Europe. Therefore, we aimed to investigate the in vitro activity of dalbavancin against different van-genotypes, with particular focus on vanB-type E. faecium. Dalbavancin susceptibility was determined for 25 van-negative, 50 vanA-positive, and 101 vanB-positive clinical E. faecium isolates (typed by cgMLST). Epidemiological Cut-Off Values (ECOFFs) were determined using ECOFFinder. For vanB-type E. faecium isolates, dalbavancin MICs were similar to those of vancomycin-susceptible isolates reaching values no higher than 0.125 mg/L. ECOFFs for van-negative and vanB-positive isolates were 0.5 mg/l and 0.25 mg/L respectively. In contrast, E. faecium possessing vanA predominantly showed dalbavancin MICs >8 mg/L, therefore preventing the determination of an ECOFF. We demonstrated the potent in vitro activity of dalbavancin against vancomycin-susceptible and vanB-type E. faecium. On the basis of the observed wildtype distribution, a dalbavancin MIC of 0.25 mg/L can be suggested as a tentative ECOFF for E. faecium.